2016
DOI: 10.1002/2016ja022891
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic field modification to the relativistic runaway electron avalanche length

Abstract: This paper explores the impact of the geomagnetic field on the relativistic runaway electron avalanche length, λe−. Coleman and Dwyer (2006) developed an analytical fit to Monte Carlo simulations using the Runaway Electron Avalanche Model. In this work, we repeat this process but with the addition of the geomagnetic field in the range of [100,900]/n μT, where n is the ratio of the density of air at altitude to the sea level density. As the ambient electric field approaches the runaway threshold field (Eth≈284… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
(59 reference statements)
0
6
0
Order By: Relevance
“…is lower than ∼50 μT for latitudes below 30°(e.g., Finlay et al, 2010), which encompasses Fermi's orbit. Cramer et al (2016) have shown that the dynamics of RREAs (e.g., RREA rates, characteristic lengths, and speed) would not be significantly modified in such low magnetic fields. Moreover, the electric field threshold above which RREAs can develop is known to be E th ¼ 2.8×N/ N 0 kV/cm (e.g., Dwyer et al, 2012), where N is the local air density and N 0 is the air density at ground level.…”
Section: Deviation Of Rreas In Homogeneousmentioning
confidence: 99%
See 1 more Smart Citation
“…is lower than ∼50 μT for latitudes below 30°(e.g., Finlay et al, 2010), which encompasses Fermi's orbit. Cramer et al (2016) have shown that the dynamics of RREAs (e.g., RREA rates, characteristic lengths, and speed) would not be significantly modified in such low magnetic fields. Moreover, the electric field threshold above which RREAs can develop is known to be E th ¼ 2.8×N/ N 0 kV/cm (e.g., Dwyer et al, 2012), where N is the local air density and N 0 is the air density at ground level.…”
Section: Deviation Of Rreas In Homogeneousmentioning
confidence: 99%
“…This is presumably the reason that the effect of geomagnetic field on RREAs has seldom been studied, with notable exceptions. Lehtinen et al (1999) and Cramer et al (2016) have quantified RREA rates in the presence of a magnetic field. From these papers, it can be seen that the strength of the geomagnetic field (<50 μT) is not sufficient to have a significant effect on RREA rates.…”
Section: Introductionmentioning
confidence: 99%
“…The electric fields used in the simulation were normalized by the threshold value for which electrons run away, E th = 286 kV/m. This value is higher than the break even field ( E b = 215 kV/m), which is the strength where minimum ionizing electrons lose energy [ Cramer et al , ]. Note that the calculations to obtain these values are done for an atomic number density of air equal to 5.39 × 10 25 atoms/m 3 .…”
Section: Model Descriptionmentioning
confidence: 99%
“…REAM is a three-dimensional Monte Carlo simulation of the relativistic runaway electron avalanche (also referred to as runaway breakdown), including electric and magnetic fields (Dwyer, 2003(Dwyer, , 2007Cramer et al, 2016). This code is inspired by earlier work by Lehtinen et al (1999) and takes accurately into account all the important interactions involving runaway electrons, including energy losses through ionisation, atomic excitation and Møller scattering.…”
Section: Reammentioning
confidence: 99%